2014
DOI: 10.4077/cjp.2014.bab155
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Testicular Damage by Daily Methamphetamine Administration in Rats

Abstract: Methamphetamine (METH)-induced brain damage and apoptosis within the central nervous system are well documented. This study was conducted to investigate the toxic effects of daily METH administration on the testes in a rat model. Male Sprague-Dawley rats (5 weeks old, ~100 g, n = 64) were divided into two groups and treated with vehicle (saline, control) or METH (10 mg/kg) for 15, 30, 60 and 90 days. The results showed that daily administration of METH decreased the body, testicular and epididymis weights as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…The hypothalamic-pituitary-gonadal axis can be affected by many factors. Chemicals including drugs can decrease fertility and even lead to infertility in both males and females by disrupting the normal function of this axis [41]. It has been shown that antiepileptic drugs also influence hypothalamic-pituitary-gonadal axis and cause reproductive dysfunction [6, 36–38, 4244].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothalamic-pituitary-gonadal axis can be affected by many factors. Chemicals including drugs can decrease fertility and even lead to infertility in both males and females by disrupting the normal function of this axis [41]. It has been shown that antiepileptic drugs also influence hypothalamic-pituitary-gonadal axis and cause reproductive dysfunction [6, 36–38, 4244].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in serum LH levels can directly decrease the testosterone production from Leydig cells [40]. Additionally, a decrease in testosterone levels is considered to be related to the severity of spermatogenic cell damage and disruptions in spermatogenesis, and can therefore cause reproductive dysfunction [40, 41]. Histopathological findings in our study also indicated that vacuolization that was mildly observed in our low-dose group was followed by cellular swelling, spermatid damage, degeneration, and necrosis becoming more pronounced in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported impairments of testis, sperm quality and endocrine disruption after METH exposure 7-10. Apoptosis of Leydig cells and a decrease of serum testosterone were found 8, 9. Furthermore, METH administration resulted in the reduction of progesterone and estrogen receptor expression in testis 9.…”
Section: Introductionmentioning
confidence: 96%
“…It is also suggested that MA affects male reproductive function at multiple levels due to its effects on the endocrine control of spermatogenesis (13, 14). Recently, it has been reported that MA decreases normal sperm morphology and count, as well as increase apoptotic cells in seminiferous tubules (15, 16). In a study conducted by Zuloaga et al , histopathological and histomorphometric alterations in seminiferous tubules have been reported in MA-treated animals (17).…”
Section: Introductionmentioning
confidence: 99%